Development of minimum competency assessment (AKM) numeracy test instruments containing ethnomathematics in elementary schools - Yashinta Arum Surya Rahartiningsih; Achmad Buchori; Sumarno (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
Minimum Competency Assessment (AKM) is an evaluation tool used to determine the quality of a school through an educational report. This study aims to describe the process of developing ethnomathematics-loaded AKM test instruments and analyze their validity, practicality, and effectiveness. This study uses a development research approach using the ADDIE model, namely, (1) Analysis, (2) Design, (3) Development, (4) Implementation and (5) Evaluation. The research subjects involved 50 fifth-grade students at SDN Ujungnegoro 01 and SDN Wonokerso 02. The validation results from the validators showed a percentage of 95%, meeting the criteria of being very valid and suitable for testing, while the results of the validity of the items 30 out of 40 questions proved valid. The practicality test obtained an average score of 84% in the good category, and the practicality/readability response by the class teacher obtained a score of 93.06 in the excellent category. Based on peer assessment, the score was obtained with an interval of 91.67 in the excellent category. The effectiveness test is based on the questions' reliability, differentiating power, and difficulty level. The reliability test results from a Cronbach Alpha value of 0.874 indicate that the assessment instrument is highly reliable. The results of the differentiating power test were 14 questions in the sufficient category and 16 in the good category. Based on the results of the 30-question level test, there are eight questions in the easy category, 19 in the medium category, and three in the difficult category. The results showed that the developed numeracy AKM test instrument is valid, practical, and effective.